2012
DOI: 10.1097/cad.0b013e32834bfd68
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide inhibits Ewing’s sarcoma cell invasiveness by targeting p38MAPK and c-Jun N-terminal kinase

Abstract: Ewing's sarcoma is the second most frequent primary malignant bone tumor, mainly affecting children and young adults. The notorious metastatic capability of this tumor aggravates patient mortality and remains a problem to be overcome. We investigated the effect of arsenic trioxide (As₂O₃) on the metastasis capability of Ewing's sarcoma cells. We performed 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide assays to choose appropriate concentrations of As₂O₃ for the experiments. Migration, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…MAPKs are potential ROS response factors, nonetheless, p-JNK and p-p38 were not involved in ATO-induced cell death in our H841 cell line model (data not shown), which is different from other cancer models (69)(70)(71). Although upregulated p-Erk1/2 was detected after ATO treatment in H841 cells, specific Erk inhibitor PD98059 failed to revert the effects induced by ATO on MMD and cell death.…”
Section: Discussionmentioning
confidence: 54%
“…MAPKs are potential ROS response factors, nonetheless, p-JNK and p-p38 were not involved in ATO-induced cell death in our H841 cell line model (data not shown), which is different from other cancer models (69)(70)(71). Although upregulated p-Erk1/2 was detected after ATO treatment in H841 cells, specific Erk inhibitor PD98059 failed to revert the effects induced by ATO on MMD and cell death.…”
Section: Discussionmentioning
confidence: 54%
“…Comparing to normal sample, OS and metastatic OS showed higher activity in cell cycle, cell differentiation, tumor metastasis, and MYC pathway. Moreover, metastatic OS owed higher MAPK signaling pathway activity than non-metastatic OS, supporting the viewpoint that MAPK signaling pathway abnormality is highly correlated to Ewing's sarcoma invasion [24], the potential main factor for metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of at least six MAPK in yeast suggests that there are more in mammals: extracellular signal-regulated kinases (ERK1, ERK2), c-Jun N-terminal kinases (JNKs), p38 isoforms, ERK5, ERK3/4, ERK7/8. In vivo and in vitro studies have confirmed that three major subgroups of MAPK including ERK1/2, JNK, and p38, are specifically involved in invasion and metastasis [9,10,62].…”
Section: Mapk Pathwaymentioning
confidence: 93%
“…Cellular migration and invasion mechanism are commonly thought to be associated with Rho family GTPases [2][3][4], JAK-STAT [5][6][7], MAPK [8][9][10], Wnt [11][12][13], Notch pathway [14][15][16]. Recently, epithelial-mesenchymal transition (EMT) programs have become the focus of the mechanism of metastasis [1,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%